Potential noxious effect of mentha aquatica L. on mitochondrial bioenergetics - Ferreira, Fernanda M. (2015)
Mentha aquatica (water mint) extracts are regularly used in food flavoring and pharmacology. In the present study, the possible effects of an ethanolic extract from leaves of M. aquatica L. on rat liver mitochondria bioenergetics were evaluated. The plant extract (up to 25 µg.mg protein-1) but not the vehicle, inhibited the mitochondrial oxidative system, as seen by a depression of respiration (state 3, respiratory control ratio (RCR), FCCP-stimulated respiration) and lower generation of the transmembrane electric potential using glutamate + malate or succinate as respiratory substrates. The depressing effects in oxidative phosphorylation can probably be related with the polyphenolic composition of the extract (mainly eriodictyol-7-O-rutinoside, luteolin-7-O-rutinoside, naringenin-7-O-rutinoside, hesperitin-7-O-rutinoside and rosmarinic acid), that can interact with membrane and change the inner mitochondrial membrane lipidic moiety. Despite decreasing the RCR, the presence of M. aquatica extract did not affect the mitochondrial phosphorylative capacity, as estimated by the ADP/O ratio. No significant increase in inner mitochondrial membrane permeability was observed and induction of mitochondrial permeability transition pore was not altered in the range of concentrations tested (up to 25 μg.mg protein-1) either. For the highest concentrations tested (25 μg.mg protein-1 or higher) the inhibition observed on the mitochondrial respiratory chain, as reflected by FCCP-stimulated respiration, revealed that M. aquatica ethanolic extract is toxic for mitochondrial bioenergetics. In conclusion, the present study suggests that a highly daily consumption of an ethanolic extract of M. aquatica leaves should be regarded as hazardous.